Enzymatic synthesis of glycosides: from natural O- and N-glycosides to rare C- and S-glycosides - Ati, Jihen; Lafite, Pierre; Daniellou, Richard (Beilstein Journal of Organic Chemistry, 2017)
Carbohydrate related enzymes, like glycosyltransferases and glycoside hydrolases, are nowadays more easily accessible and are thought to represent powerful and greener alternatives to conventional chemical glycosylation procedures. The knowledge of their corresponding mechanisms has already allowed the development of efficient biocatalysed syntheses of complex O-glycosides. These enzymes can also now be applied to the formation of rare or unnatural glycosidic linkages.
Keywords: enzyme; glycochemistry; glycoside hydrolase; glycosyltransferase; mechanism